The epidemiology of the primary brain tumors in Rostov region in 2010-2015 - I. V. Balyazin-Parfenov; V. A. Balyazin; T. V. Shelyakina; O. V. Tarnopolskaya (Кубанский научный медицинский вестник)
The dynamics of the prevalence, incidence, and clinical and statistical characteristics of primary and metastatic brain tumors (BT) with regard to their histological types in the Rostov region, depending on the environmental conditions of life, different age and gender and social groups who were treated in specialized and non-specialized hospitals of Rostov-on-Don for the period from 1 january 2010 to 2015 is a proven result. A further increase in the level of incidence of malignant brain tumors, both due to the improved diagnostics of tumor diseases of the brain, and the influence of climatic, demographic, environmental and medico-social characteristics of the study region were showed. However, many epidemiological aspects of neoplastic diseases of the brain remains poorly understood, requires the continuation of this study.